2017
DOI: 10.20429/ijsotl.2017.110210
|View full text |Cite
|
Sign up to set email alerts
|

Not-so-critical friends: Graduate student instructors and peer feedback

Abstract: Graduate student instructors (henceforth, instructors) Cover Page FootnoteThis paper is an expansion of work previously presented at the Conference for Research in Undergraduate Mathematics Education. The author thanks Karla Childs and Natasha Speer for their thoughtful comments on an earlier version of the manuscript. Graduate student instructors (henceforth, instructors) play a crucial role in teaching early STEM courses. Thus, professional development for these instructors addresses an urgent need to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Without a disparity in power or concern about performance being judged by a more experienced other or against potentially constraining criteria, the GTAs in this project were less intimidated (as Nadine suggests) and experienced many of the benefits identified in studies of this area. In particular, there was a sense of reassurance and feeling less alone, as reported by Reinholz (2017) and Hendry et al (2014). Supporting findings by Torres et al (2017), the observations and following learning conversations encouraged the sharing of practices and motivated the GTAs to reflect on their individual methods and, in some cases, their disciplinary approaches too.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Without a disparity in power or concern about performance being judged by a more experienced other or against potentially constraining criteria, the GTAs in this project were less intimidated (as Nadine suggests) and experienced many of the benefits identified in studies of this area. In particular, there was a sense of reassurance and feeling less alone, as reported by Reinholz (2017) and Hendry et al (2014). Supporting findings by Torres et al (2017), the observations and following learning conversations encouraged the sharing of practices and motivated the GTAs to reflect on their individual methods and, in some cases, their disciplinary approaches too.…”
Section: Discussionmentioning
confidence: 60%
“…By contrast, a growing body of evidence suggests that when GTAs have been involved in peer (specifically equal-status) observation or peer review of teaching projects, there are significant benefits to the development of their self-critique and reflective thinking skills (Reinholz, Cox and Croke, 2015;Howlett and Nguyen, 2020). Reinholz's (2017) study of Mathematics GTAs also found that observing and giving feedback to each other encouraged them to feel less isolated in their roles and part of a professional learning community sharing similar worries, concerns and challenges.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
See 1 more Smart Citation
“…Research has yielded mixed findings regarding peer critiques. The quality of peer critique has been a concern of educators (Chambers et al, 2014; Choi, 2014; Mutch et al, 2018; Nilson, 2003; Sandvoll, 2014; Schneider & Andre, 2007; Reinholz, 2017). Smith (2017) pointed out: “The most pernicious is the quality of the feedback.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A key component of experiential learning is reflection: the act of processing an experience, action, or practice to gain further insight into the experience to better inform and guide future actions (Reinholz, 2016). Reflection is seen as a fundamental component of teacher education, to help teachers develop reflective practice (e.g., Averill, Drake, Anderson, & Anthony, 2016;Reinholz, 2017;Sherin, Jacobs, & Philipp, 2011).…”
Section: Introductionmentioning
confidence: 99%